2018
DOI: 10.3390/catal8120608
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fe/Al2O3 Catalysts for the Reverse Water-Gas Shift Reaction: On the Effect of Cs as Activity/Selectivity Promoter

Abstract: The conversion of CO2 into CO via the Reverse Water–Gas Shift (RWGS) reaction is a suitable route for CO2 valorisation. Fe-based catalysts are highly active for this reaction, but their activity and selectivity can be substantially boosted by adding Cs as a promoter. In this work we demonstrate that Cs modifies the redox behaviour and the surface chemistry of the iron-based materials. The metallic dispersion and the amount of metallic Fe centres available for the reaction depends on Cs loading. 5 wt. % of Cs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…Noble metal catalysts, mainly Pt and Rh based supported catalysts, have high activity towards hydrogen dissociation, relatively moderate strength with the adsorption of reaction intermediates and the incompletely filled D‐orbital electrons make them easier for the adsorption of reactants with moderate strength, which is further benefiting to form the intermediate “active compound” in RWGS reaction . Besides mentioned catalysts other metal catalysts as active components or as supports are Pd, Ni, Co, Fe, Fe supported on CNTs and carbide (Mo 2 C) catalyst …”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
“…Noble metal catalysts, mainly Pt and Rh based supported catalysts, have high activity towards hydrogen dissociation, relatively moderate strength with the adsorption of reaction intermediates and the incompletely filled D‐orbital electrons make them easier for the adsorption of reactants with moderate strength, which is further benefiting to form the intermediate “active compound” in RWGS reaction . Besides mentioned catalysts other metal catalysts as active components or as supports are Pd, Ni, Co, Fe, Fe supported on CNTs and carbide (Mo 2 C) catalyst …”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
“…Indeed, it is generally known that the stabilization of Cu δ+ sites, as specific active centers for CO 2 adsorption/activation, can be attributed either to the incorporation of the copper phase into the metal-oxide lattice or to the formation of a definite metal-support interaction, suitable to promote and ensure the progressive hydrogenation rate of CO 2 via several intermediates and transition states until methanol. On the contrary, an evidently weak CO x adsorption on the catalytic surface sites prevents the sequential hydrogenation via C-O bond dissociation, while enhancing the parallel path of RWGS [29,30]. Since the molar fraction of Zn also affects the metallic properties of the catalyst (see Figure 4), a further elaboration was carried out, considering the rate of methanol formation as a function of the N 2 O/CO 2 ratio, taken as a parameter capable of justifying the relative redox contribution of metallic sites with respect to sites of oxide nature (see Figure 9).…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…Literature reports can provide a first explanation to this phenomenon, since it has been shown that alkali promoters contribute to weaken the CO adsorption on catalyst's surface, hindering its further hydrogenation into CH 4 . [ 94 ] We will see later on that this result can be rationalized if we consider the charge transfer between the support and the ruthenium (see Section 2.2.3, Figure 9). Second, the CO selectivity increases with ToS at the three temperatures investigated, and this effect is more accentuated in the case of the catalyst not promoted by sodium.…”
Section: Resultsmentioning
confidence: 86%